Pediatric Diabetes Consortium Type 1 Diabetes New Onset (NeOn) Study: factors associated with HbA1c levels one year after diagnosis. Issue 4 (24th July 2013) - Redondo, Maria J; Connor, Crystal G; Ruedy, Katrina J; Beck, Roy W; Kollman, Craig; Wood, Jamie R; Buckingham, Bruce; Klingensmith, Georgeanna J; Silverstein, Janet; Tamborlane, William V; for the Pediatric Diabetes Consortium
Abstract Objective To identify determinants of hemoglobin A1c (HbA1c) levels 1 yr after the diagnosis of type 1 diabetes (T1D) in participants in the Pediatric Diabetes Consortium (PDC) T1D New Onset (NeOn) Study. Research design and methods: Diabetes‐specific as well as socioeconomic factors during the first year following diagnosis were analyzed in 857 participants (mean age 9.1 yrs, 51% female, 66% non‐Hispanic White) not participating in an intervention study who had an HbA1c value at 12 months. Result Mean ± SD HbA1c at 1 yr was 62 ± 16 mmol/mol (7.8% ± 1.5). In univariate and multivariate analyses, clinical center, non‐Hispanic White race, private health insurance, living with both parents, higher frequency of self‐monitoring of blood glucose (SMBG), and lower insulin requirements were associated with lower HbA1c concentrations at 1 yr (p < 0.01). No association was found with gender, age, Tanner stage, body mass index (BMI), diabetic ketoacidosis (DKA) at onset, number of positive autoantibodies or HbA1c at onset, or number of visits to diabetes physician during the first year. Conclusions White race, higher socioeconomic status, two‐parent household, more frequent SMBG, and low insulin requirements are associated with lower HbA1c concentration 1 yr after the onset of T1D in children.